Pelaku Usaha Mengoptimalkan Keuntungan Melalui Pelatihan Perhitungan Laba Rugi Produk dan Jasa - Oktaviani, Ayu Aulia; Herawaty, Vinola; Supriyadi, Yadi; Indradjid, Deliza Henny; Satria, Roy Gembira; Zulkarnaen, Risa Fitriandi (Penerbit Goodwood, 2025)
Purpose: This training aims to increase participants' understanding of calculating profit and loss for products and services to optimize business profits in small and medium businesses according to applicable accounting standards. Methodology/approach: The training was held at Sekolah Kewirausahaan Bina Amanah Cordova in December 2023 and was attended by 18 participants. This activity uses training and counseling methods supported by tools and equipment such as projectors and laptops, with activity stages that include presentation material, calculation simulations, question and answer sessions, and group discussions. Results/findings: Based on the results of the questionnaire, it can be seen that this training had a positive impact on participants' understanding of preparing profit and loss reports and making simple financial reports, although there were several challenges related to limited time and limited individual assistance. Conclusions: This training has proven effective in increasing the basic understanding of MSME actors in preparing simple financial reports and can be a strategic solution to overcome accounting limitations through an applied and sustainable approach. Limitations: The limitations of this study are that the sample only includes participants from SKBA Cordova in Pondok Aren; therefore, the results may not represent all MSMEs in Indonesia. Moreover, the short training duration and evaluation based solely on post-training questionnaires were insufficient to fully reflect participants’ improvement in accounting skills. Contribution: This training shows great potential for helping business people optimize their financial management. Future recommendations include continued training, individual mentoring, and the development of online training modules